Sia Tō’onga Mo’ui study : New Zealand Pacific lifestyle programme : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Public Health at Massey University, Wellington, New Zealand - Faeamani, Gavin (Massey University, 2024)
Objective and Rationale: Pacific peoples in Aotearoa New Zealand (NZ) have the highest rates of type 2 diabetes (T2DM) compared to other population groups (1). There is a paucity in the design and implementation of culturally tailored approaches in New Zealand focused on targeting major long-term conditions and particularly in reducing the T2DM epidemic among high-risk population groups. This doctoral study investigates a culturally tailored approach focused on reducing the risk of developing T2DM. The objective of this study was to implement a culturally relevant lifestyle change programme by adapting the efficacious Diabetes Prevention Programme (DPP) for use specifically amongst Tongans living in New Zealand. It also seeks to explore and understand the uptake and acceptability of the adapted prevention programme, including identifying the enablers and barriers of the programme in reducing the progression of prediabetes to T2DM in Tongan adults, aged 18-74 years old. Methods: The Sia Tō’onga Mo’ui Diabetes Prevention Programme (STM-DPP) uses a mixed-method approach and includes three phases. Phase 1: uses a citizen’s panel approach, composed of three panel groups made up of community members, (ii) health experts, and (iii) representatives from the first two panels to adapt the Pacific Island Diabetes Prevention Programme (PI-DPP). Phase 2 involves the implementation of the newly adapted, now known as the STM-DPP, by improving diet via weekly Zoom sessions and doing 150 minutes of physical activity every week, aiming to reduce 5% or more of total body weight. Data on clinical markers at baseline and post-programme were collected and analysed to determine the impact of the STM-DPP. Phase 3 included an evaluation of the STM-DPP using focus groups aimed at examining successful processes, benefits, practical applications, behavioural, cultural, and motivational drivers of change. Setting: The study was conducted in Auckland, NZ. Focus group discussions on Zoom were employed due to the restrictions of COVID-19 at the time and associated lockdowns that restricted any face-to-face or in-person meetings. The PI-DPP modules were also being presented weekly on Zoom, with exercise sessions held at the two study site venues. Results: The citizen panels guided the adaptation of the PI-DPP to reflect the Tongan culture and way of life; duration of the programme; consolidate and adapt the contents of the modules; appropriateness of programme delivery and approach; and incentives for participants. The implementation of the STM-DPP included 41 Tongan participants (males = 25, females = 16), of whom 95.2% had BMI≥30.0 and 75.6% had a Prediabetes Risk Test (PRT) score of baseline PRT≥5, indicating a high risk. At the conclusion of the intervention, post-programme data revealed significant changes across all areas for participants in weight, waist-to-height ratio, physical activity capability, and blood pressure. The evaluation of the STM-DPP also reports that the program’s feasibility and acceptability among the Tongan communities were positive, which explained the high uptake of the programme. Conclusions: These results provide evidence-based research affirming that the culturally adapted T2DM prevention programme, STM-DPP, is feasible and acceptable amongst Tongans in NZ. The positive impact of the prevention programme among the Tongan population in Auckland could be made available and adapted to other Pacific populations across NZ.
Keywords: Public Health; 451618 Pacific Peoples sport and physical activity; 451821 Pacific Peoples social impact and program evaluation